Magnetic Moments of States in 110Sn - Kumbartzki, G J (Journal of physics. Conference series, 2016)
The semi-magic Sn isotopes with Z = 50 are the subject of extensive experimental and theoretical studies. The measured B(E2) values to the 21+ states for the neutron-deficient side of the isotope chain suggest enhanced collectivity when fewer particles are available if the proton shell is not broken. Magnetic moments which are sensitive to proton and neutron contributions to the wave functions of the states could provide critical and relevant information. Magnetic moments were previously measured only for the even stable and a few neutron-rich unstable Sn isotopes. A measurement of the g factors of excited states in 110Sn using the transient field technique was performed at the 88-Inch Cyclotron at the LBNL in Berkeley. The 110Sn nuclei were produced via an α-particle transfer to 106Cd.